DISTRIBUSI KEPEMILIKAN LAHAN PERTANIAN DAN ANALISIS PENDAPATAN PETANI DI WILAYAH PEDESAAN (Studi Kasus di Desa Kepanjen Kecamatan Gumukmas Kabupaten Jember) - Vivi Trisna Handini; M. Rondhi (UPT Penerbitan Universitas Jember, 2018)
The essential factor in conducting agricultural activities is the land. The function of the agricultural land is not only as a productive asset but also as a product that can be used to be traded. This condition happened in one of villages in Jember regency, that was Kepanjen. The effect of land trading was the change of agricultural land tenure. This change would cause the land tenure distribution and also influence the farmer economic condition through their income. The aims of this research were to know the agricultural land tenure distribution and farming income in Kepanjen by using gini index ratio on 43 farmers. Based on the result of the research, it was known that the agricultural land tenure distribution in Kepanjen was in lame category with 0.51 gini index value. The income received by the farmers was differentiated based on 2 planting patterns. The first planting pattern (paddy and palawija) had average income as much as Rp 18.738. 494 / year, while, the second planting pattern (paddy, palawija and horticulture) had average income as much as Rp 27.768.630 / year. The income distribution in Kepanjen showed the unequal condition with 0.67 gini coefficient ratio.